2011
DOI: 10.1159/000322258
|View full text |Cite
|
Sign up to set email alerts
|

Three Days Rush Venom Immunotherapy in Bee Allergy: Safe, Inexpensive and Instantaneously Effective

Abstract: Background: Rush venom immunotherapy (VIT) is highly effective in vespid venom allergy, but comparable data regarding bee venom (BV) allergy are sparse. We evaluated its safety, efficacy and cost in BV-allergic patients. Methods: Conventional or rush VIT were offered to all patients with systemic reaction to insect sting. Rush VIT was also given to hyperreactive patients who failed to reach the maintenance dose with conventional VIT due to multiple systemic reactions. In BV-allergic patients, honeybee sting ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Others found that RVIT was as safe as CVIT, especially in vespid venom allergy [22]. We have demonstrated in the past the safety and efficiency of our rush build-up protocol in the general population as well as in children, including very young children, when most of the patients were allergic to BV [8,23]. Thus, in accordance with our previous findings, the current study also found a lower incidence of SR per injection in patients receiving RVIT compared to CVIT despite the fact that all of the patients with a high baseline tryptase level, which is known to be a major risk factor for VIT- ISR, were in the RVIT group.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Others found that RVIT was as safe as CVIT, especially in vespid venom allergy [22]. We have demonstrated in the past the safety and efficiency of our rush build-up protocol in the general population as well as in children, including very young children, when most of the patients were allergic to BV [8,23]. Thus, in accordance with our previous findings, the current study also found a lower incidence of SR per injection in patients receiving RVIT compared to CVIT despite the fact that all of the patients with a high baseline tryptase level, which is known to be a major risk factor for VIT- ISR, were in the RVIT group.…”
Section: Discussionmentioning
confidence: 85%
“…This rate was significantly higher in the RVIT group compared to the CVIT group (35 [100%] and 24 patients [82.7%], respectively; p = 0.01). We were not able to reach the full maintenance dose in 5 patients of the CVIT group due to recurrent SR. As previously described [8,9], all of the patients who failed to reach the maintenance dose by CVIT were offered RVIT. Four patients who consented underwent a recurrent build-up phase with RVIT and reached the 100-μg maintenance dose uneventfully.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various dose titration protocols have been suggested for the initiation of VIT [9,10]. The aim is to achieve rapid protection, especially during the flight time of the insects [11].…”
Section: Discussionmentioning
confidence: 99%